Metal-Based Nanoparticles for Cancer Metalloimmunotherapy - Ivan Hardianto Suliman; Kidong Kim; Weihsuan Chen; Yubin Kim; Jeong-Hyun Moon; Sejin Son; Jutaek Nam (MDPI AG, 2023)
Although the promise of cancer immunotherapy has been partially fulfilled with the unprecedented clinical success of several immunotherapeutic interventions, some issues, such as limited response rate and immunotoxicity, still remain. Metalloimmunotherapy offers a new form of cancer immunotherapy that utilizes the inherent immunomodulatory features of metal ions to enhance anticancer immune responses. Their versatile functionalities for a multitude of direct and indirect anticancer activities together with their inherent biocompatibility suggest that metal ions can help overcome the current issues associated with cancer immunotherapy. However, metal ions exhibit poor drug-like properties due to their intrinsic physicochemical profiles that impede in vivo pharmacological performance, thus necessitating an effective pharmaceutical formulation strategy to improve their in vivo behavior. Metal-based nanoparticles provide a promising platform technology for reshaping metal ions into more drug-like formulations with nano-enabled engineering approaches. This review provides a general overview of cancer immunotherapy, the immune system and how it works against cancer cells, and the role of metal ions in the host response and immune modulation, as well as the impact of metal ions on the process via the regulation of immune cells. The preclinical studies that have demonstrated the potential of metal-based nanoparticles for cancer metalloimmunotherapy are presented for the representative nanoparticles constructed with manganese, zinc, iron, copper, calcium, and sodium ions. Lastly, the perspectives and future directions of metal-based nanoparticles are discussed, particularly with respect to their clinical applications.